Workshop Design on Fast Fashion Impacting Sustainability - Ira Permatasari; Wulan Madani Aisyiyah; Fia Izzah Maylinda; Nora Hafildah (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Fast fashion has raised sustainable issues in the clothing cycle from the production stage to the stage after the clothes are worn and end up generating waste. Therefore, it is necessary to adopt a sustainable approach to overcome practices that damage the ecology. This research uses qualitative methods by means of observation, literature studies, questionnaires, interviews, and the design process using Gustami theory (observation, design, manufacturing process). This research will involve several communities and their contributions to fast fashion and sustainable fashion in Indonesia to find out how much they understand about fast fashion as well as the concept of sustainable that can minimize the negative impact of fast fashion. The results of the survey above discussed public awareness and behavior towards fast fashion, as many as 62.7% of respondents knew the impact of the dangers of the fashion, while there were 29.4% of respondents who did not know the issue of fashion. However, the circumstances and conditions that result in the lack of sensitivity of the community to the environment resulted in a lack of knowledge and doubt about the issue. The data of the respondents who do not know and doubt, the need for an equitable education about this issue and the impact on the environment through media event workshops as information channels.